Male and female brain evolution is subject to contrasting selection pressures in primates - Dunbar, Robin IM (BioMed Central, 2007)
The claim that differences in brain size across primate species has mainly been driven by the demands of sociality (the "social brain" hypothesis) is now widely accepted. Some of the evidence to support this comes from the fact that species that live in large social groups have larger brains, and in particular larger neocortices. Lindenfors and colleagues (BMC Biology 5:20) add significantly to our appreciation of this process by showing that there are striking differences between the two sexes in the social mechanisms and brain units involved. Female sociality (which is more affiliative) is related most closely to neocortex volume, but male sociality (which is more competitive and combative) is more closely related to subcortical units (notably those associated with emotional responses). Thus different brain units have responded to different selection pressures.